2008
DOI: 10.1017/s0007114508020369
|View full text |Cite
|
Sign up to set email alerts
|

Whole-grain consumption and transcription factor-7-like 2 (TCF7L2) rs7903146: gene–diet interaction in modulating type 2 diabetes risk

Abstract: Whole grains are known to influence postprandial glucose response and insulin demand and are inversely associated with diabetes risk. Genetic variation of the transcription factor-7-like 2 encoding gene (TCF7L2) is assumed to promote an early insulin secretory defect and has been consistently attributed to the risk of developing type 2 diabetes. The present study examined the hypothesis that the protective effect of whole grains might be attenuated in the presence of the rs7903146 risk-conferring T-allele. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
73
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(82 citation statements)
references
References 17 publications
(16 reference statements)
6
73
0
3
Order By: Relevance
“…While this is the case in other population groups, some studies reported a weak 33,34 or no association [35][36][37][38] . Other studies highlighted the effect of the TCF7L2 polymorphisms on the progression of T2DM 35,39 , in some ethnic population groups these variants were associated with responses to medication 40,41 , and in others their effect on the disease was modulated by the type of diet [42][43][44] .Our results [1.43 (1.00 to 2.04), p= 0.053] are comparable to those reported for other African ethnic population groups 17,18,20 . It is possible that TCF7L2 polymorphisms have different effects in various ethnic population groups depending on the diet.…”
Section: Discussionsupporting
confidence: 80%
“…While this is the case in other population groups, some studies reported a weak 33,34 or no association [35][36][37][38] . Other studies highlighted the effect of the TCF7L2 polymorphisms on the progression of T2DM 35,39 , in some ethnic population groups these variants were associated with responses to medication 40,41 , and in others their effect on the disease was modulated by the type of diet [42][43][44] .Our results [1.43 (1.00 to 2.04), p= 0.053] are comparable to those reported for other African ethnic population groups 17,18,20 . It is possible that TCF7L2 polymorphisms have different effects in various ethnic population groups depending on the diet.…”
Section: Discussionsupporting
confidence: 80%
“…Clinical scenario 1: cumulative effect of multiple genomic markers and T2D. The EPIC-Potsdam study 8 was a prospective case-cohort design with 773 individuals with T2D and 2,225 randomly selected population-based controls followed for an average of 7.1 years ( Table 3). The risk of developing T2D was associated with the TCF7L2 T allele (hazard ratio: 1.51) and was compared with daily consumption of whole grains stratified by TCF7L2 genotype.…”
Section: Clinical Utilitymentioning
confidence: 99%
“…The NUGENOB study 9 was a multicenter randomized openlabel trial that compared the benefits of two dietary interventions 8 with intermediate outcomes relevant to T2D. Only the surrogate outcome of plasma fasting glucose is relevant to this review.…”
Section: Clinical Utilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Given that randomized trials have demonstrated that changing lifestyle factors (e.g., weight loss, improved diet, and increased physical activity) can result in decreased risk for diabetes, the possible knowledge of an individual's T2D increased risk by genetic testing could improve overall health outcomes. [8][9][10][11][12][13][14][15] descriptions of tests and intended use claims Four companies offering five genomic tests for T2D were identified in July 2010, and any update to the panels was verified in July 2012. The test panels included between 1 and 28 genes ( Table 1) on one or more panels.…”
Section: Background and Clinical Context For The Recommendationmentioning
confidence: 99%